2015
DOI: 10.12657/steciana.018.015
|View full text |Cite
|
Sign up to set email alerts
|

Natural valorization of degraded swamp-originating meadows of Lower Silesia (Extension of the Oświt method)

Abstract: Swamp-originating meadows constituting indirect habitats between living peatlands and classical grasslands may be difficult to evaluate. An indiscriminate application of the oświt (2000) method for their valorization does not fully reflect their value, because of flora which is different from flora found in living peatlands (in particular, the invasion of less hygrophilous flora). Based on the research carried out in the years 2005-2010 on eight swamp-originating meadow complexes, the scale was elaborated whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…tomentosa is found in wet meadows, wet forests and bogs. It has rapidly become a major threat to habitats of high conservation value (Podlaska 2014b; Wiatrowska & Danielewicz 2016), and several studies have reported significant impacts on native species composition and diversity (Podlaska 2014a,b; Wiatrowska & Danielewicz 2016; Balkenhol et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…tomentosa is found in wet meadows, wet forests and bogs. It has rapidly become a major threat to habitats of high conservation value (Podlaska 2014b; Wiatrowska & Danielewicz 2016), and several studies have reported significant impacts on native species composition and diversity (Podlaska 2014a,b; Wiatrowska & Danielewicz 2016; Balkenhol et al . 2018).…”
Section: Introductionmentioning
confidence: 99%